Pedagogical roles of information and communication technology (ict) in language development skills: arabic panoramic approach (2012)
Towards the end of the twentieth and twenty-first centuries. It becomes apparent that national development aptly depends on science and technology. The fusion of its positive reliance in global dynamics and expanding cultural diverse to all field of human knowledge, especially to language learning skills has hitherto be the concerned of the language teachers over the years back. The usefulness of ICT, in particular the internet facilities, connection network, and its communication tools in enhancing the teaching aids and learners need cannot be over-emphasized. In the global context, language is seen as an intimate part of social identity and as a vital tools in exchanging communication thoughts, beliefs and ideals, as it has been globally applauded through its vehement roles in all spheres of human endeavors. It is very obvious that acquisition of another language as an addition to mother 's language or native language by the learners has to do with the studies in psychology and sociology of the learning process. thus, In learning languages, a distinction is usually made between mother tongues which is the original language acquiring by child directly without any transmitters, and this is referred as "Source Language", while second languages, and foreign languages, is referred as "Target Language Thus, Arabic as one of the Semitic group of language has been globally welcomed through its myriads impact in national development and human social strata. Therefore, this paper is aiming to examine the vehement roles of ICT in enhancing Arabic language learners skills. Interestingly, the Paper enunciated about the rationale for ICT and Arabic language to global phenomenon. Also, the Paper further diagnosed the semiotic enhancement of ICT to Arabic language learner skills. And proper recommendation capable of fostering the enhancement of Arabic language skills through the use of ICT would be elucidated.